Diagnosis of bovine viral diarrhea in Bubalus bubalis dairy farms - Oriana Gavidia; Rosaura Pérez-Gil (Revista Científica)
Bovine viral diarrhea (BVD) is a disease with worldwide distribution and endemic in most bovine populations, causing a wide range of clinical manifestations, including reproductive disorders, such as embryo mortality and abortions, and low milk production. The purpose of this research was to describe the situation of BVD in Bubalus bubalis females from one dairy farm, in Portuguesa state, Venezuela. Fifty-two 52 samples were taken in August 2022. From these, 22 were from a low milk yield group (3.35 ± 0.30 liters/day) and 30 from a high milk yield group (6.91 ± 0.82 liters). The farmer reported fluctuations in milk production, weak calves, the presence of blisters in the oral cavity and dead animals. The ELISA test was performed to detect BVD p80 antibody using the IDvet ® kit, and the positive cases were defined using a cut-off value sample/negative ≤ 40. The seropositive results for the non-structural protein p80, in general, were 55.76%. In the group of buffaloes with low milk yield, 54.54% were positive, while in the group with high milk yield, 53.33% were positive, with no significant  differences between animal groups (p>0.05). These results show a humoral immune response against potential BVD infections (regardless of the milk yield) since p80 is a non-structural protein that manifests during viral replication. Therefore, it is suggested to implement sanitary plans for the control of BVDV to minimize the economic losses associated with the disease.